Somatotype, body composition, and physical fitness in artistic gymnasts depending on age and preferred event - Sterkowicz-Przybycien, K.; Sterkowicz, S.; Biskup, L.; Zarów, R.; Kryst, L.; Ozimek M (PLOS ONE, 2019)
In men`s artistic gymnastics, results that are particularly appreciated are those obtained in all-around and individual events such as the floor exercise, pommel horse, rings, vault, parallel bars and horizontal bar. However, few studies have explored the dependency of anthropometric characteristics and fitness from age category or the event preferred by gymnasts. Therefore, the aim of this study is to compare the somatic type, body composition and values of some anthropometric and fitness characteristics and indices of gymnasts according to age and preferred event. A total of 53 male gymnasts (19 seniors and 34 juniors) were examined right before the Polish Senior and Junior Championships in Artistic Gymnastics in Warsaw (May 25 to 28, 2017). We examined the characteristics of body length, skeletal system mass, muscle mass, skinfold thickness, and body mass (Tanita S.C.-330S). Body composition (Durnin and Womersley equations), somatotypes (Heath-Carter methodology), handgrip strength (Takei dynamometer), body balance (UPST), the power of the lower limbs (CMJ) were evaluated. Senior gymnasts presented higher than juniors experience, mesomorphy and had higher values in fitness tests of handgrip strength and power of lower limbs (p<0.05). The specialists in floor exercises and vault characterized in higher mesomorphy and lower ectomorphy (p<0.05) and better results of CMJ (p<0.05). We concluded: The seniors demonstrated natural predominance over juniors in several somatic and fitness variables. Detected differences can be useful in the process of identification and development of gymnastic talent. The detected effect of preferred event on certain variables that characterize body build and physical fitness can be useful for choosing a specialization in gymnastic event. A high skill level in all-around events at a national competitive level can be achieved by an athlete characterized by adequate experience, a mesomorphy somatotype component, lower limb index, pelvi-acromial index and relative HGSmax.